The Effect of Flour Variations on The Organoleptic Properties of Ambon Banana Sheld Chips (Musa paradisiaca) - Agustin, Nurul Alviana; Vita Kurnia Utami (Teknologi Hasil Pertanian, Fakultas Teknik, Universitas Annuqayah, 2025)
Banana is one of the relatively large herbaceous plants with large leaves with the Musaceae family. Banana plants can be cultivated well in tropical and subtropical climates. Banana stems contain chemical compounds including saponins, tannins and flavonoids. So it can be used as a basic ingredient for making banana stem chips. Banana stem chips are used by the community to empower banana tree plants and improve the quality of chips by testing Organoleptic properties. The research method used a Completely Randomized Design (CRD) with 4 treatments P0 = Banana stem 350 gr (without using flour) P1 = Banana stem 350 gr + Cornstarch 250 gr P2 = Banana stem 350 gr + Tapioca Flour 250 gr P3 = Banana stem 350 gr + Rice Flour 250 gr. Based on the results of the color, taste and texture analysis tests, it produced a significant value of p <0.00 and it was said that there was no significant difference in banana stem chips. While the aroma of banana stem chips significance p> 0.032 and it can be said that there is a significant difference in banana stem chips and can be further tested with the Duncan test which produces P0, P1 with P2 and P3 there is a significant difference in the aroma of banana stem chips.